A life beyond the boundaries - Anderson, Benedict R. O'G. (Benedict Richard O'Gorman) 1936-2015 (Anvil Publishing Inc., 2016)
An intellectual memoir by the author of the acclaimed Imagined Communities. Benedict Anderson is one of the leading historians of nationalism and Southeast Asia. His seminal book Imagined Communities has changed the way we think about the reason that people live, die and kill in the name of nationhood. Born in China, Anderson spent his childhood in California and Ireland, was educated in England and finally found a home at Cornell University, where he immersed himself in the growing field of Southeast Asian studies. After field work in Indonesia, Thailand and the Philippines, he was banned from Suharto's Indonesia for disputing the legitimacy of the 1965 coup. In his memoir, he brings to life the intellectual formation of a life spent open to the world, resisting the easy comforts of imagined homes: the joys of learning languages; the importance of field work; the influence of the New Left upon global thinking; and the satisfactions of teaching.